PENGARUH CORPORATE SICIAL RESPONSIBILITY DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Ni Wayan Dian Yuli Artianai; I Wayan Suka Dana; I Wayan Widyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
This study had purpose to test and obtain empirical evidence of Corporate Social Responsibility effect and managerial ownership on the value of mining companies listed on the Indonesia Stock Exchange which moderated by company size. The research population was mining companies listed on the Indonesia Stock Exchange from 2016 to 2018. The samples in this study consisted of 16 mining companies which were determined based on the purposive sampling method. The analytical tool that used to test the hypothesis was multiple linear regression and Moderated Regression Analysis. The results showed that Corporate Social Responsibility had a positive and significant effect on the company value. Meanwhile, managerial ownership had not effect on company value. Company size is able to moderate the relationship between the influence of Corporate Social Responsibility and managerial ownership on company value. Further research is expected to involve other parties in determining the extent of social responsibility disclosure as material for re-examination.